Protection of XML-Based Denail-of-Service and Httpflooding Attacks in Web Services Using the Middleware Tool - Alasri, Abbas; Sulaiman, Rossilawati (International Journal of Engineering and Technology, 2018)
A web service is defined as the method of communication between the web applications and the clients. Web services are very flexible and scalable as they are independent of both the hardware and software infrastructure. The lack of security protection offered by web services creates a gap which attackers can make use of. Web services are offered on the HyperText Transfer Protocol (HTTP) with Simple Object Access Protocol (SOAP) as the underlying infrastructure. Web services rely heavily on the Extended Mark-up Language (XML). Hence, web services are most vulnerable to attacks which use XML as the attack parameter. Recently, a new type of XML-based Denial-of-Service (XDoS) attacks has surfaced, which targets the web services. The purpose of these attacks is to consume the system resources by sending SOAP requests that contain malicious XML content. Unfortunately, these malicious requests go undetected underneath the network or transportation layers of the Transfer Control Protocol/Internet Protocol (TCP/IP), as they appear to be legitimate packets.In this paper, a middleware tool is proposed to provide real time detection and prevention of XDoS and HTTP flooding attacks in web service. This tool focuses on the attacks on the two layers of the Open System Interconnection (OSI) model, which are to detect and prevent XDoS attacks on the application layer and prevent flooding attacks at the Network layer.The rule-based approach is used to classify requests either as normal or malicious,in order to detect the XDoS attacks. The experimental results from the middleware tool have demonstrated that the rule-based technique has efficiently detected and prevented theattacks of XDoS and HTTP flooding attacks such as the oversized payload, coercive parsing and XML external entities close to real-time such as 0.006s over the web services. The middleware tool provides close to 100% service availability to normal request, hence protecting the web service against the attacks of XDoS and distributed XDoS (DXDoS).\